Myanmar Household Welfare Survey Round Three: Note on Sample Characteristics and Weighting - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
The third round of the MHWS was carried out between July 8, 2022 and August 10, 2022. In the third round of MHWS, 12,128 households responded to the survey: • 5,978 households that were interviewed in Round 1, Round 2, and Round 3; • 3,063 households that were interviewed in Round 2 and Round 3; • 589 households that rejoined the sample after being interviewed in Round 1; • 2,498 households that were added to replace the 3,088 households that dropped out of the sample after Round 2. Ongoing issues with conflict and security threats made it difficult to collect data from rural lower-educated households. After weighting, the sample is not statistically different from the Round 1 and Round 2 sample in terms of household location, percent farming households, and percent lower-educated households.